Qurban Animal Purchasing System During The Covid 19 Pandemic and Marketing Strategic Implication - Silvia Dewi Sagita Andik; Pria Sembada; Annisa Hakim (School of Business, IPB University (SB-IPB), 2022)
The Indonesian Government's regulation regarding Large-Scale Social Restrictions (PSBB) has limited interaction and communication during the COVID 19 pandemic. In Indonesia, the location is separated two zones during the COVID 19 pandemic, namely red zones and green zones. The red zone is defined as an area where there are significant number of COVID 19 cases. Meanwhile green zone is an area where there are not significant number of COVID 19 cases. Eid al-Adha is a Muslim holiday that is identical to the slaughter of sacrificial animals (cows or goats). There have been changes in consumer behaviour related to the qurban animal purchasing system during the pandemic. The purpose of this study is to analyze the change of consumer behaviour in qurban purchase system and to develop the marketing strategic during the COVID 19 pandemic to minimize the risk. The survey method using online questionnaires was chosen to collect data from 100 respondents. Analysis using descriptive cross-tabulation, and SWOT analysis. The results showed that there was a change in the behaviour of the qurban animal buying system in two different zones, namely the red zone and the green zone. Most of the consumers in the red zone have shifted to buy qurban animals online, while in the green zone there has not been too much change in the shift of buying from offline to online systems. The marketing strategic for business are they can uses the digital platform for selling their product. Keywords: consumer behavior, COVID-19 Pandemic, Indonesia, SWOT, qurban animal